Biodiversity Measurement in Forests of Various Canopy Density - Jha, Prem Kumar; Nanduri, Uma (Indian Forester, 2003)
Biodiversity Index, number of different species and total number of plants of forest ecosystem having different canopy density was measured. It was found that all the three attributes decreases with the decrease in canopy density. The decrease in these attributes can be ascribed to the rapid fall in the number of tree species. Forest degradation not only causes reduction in biodiversity but also leads to the change in the community composition.